Earnings, consumption and lifecycle choices - Costas Meghir; Luigi Pistaferri (Institute for Fiscal Studies (IFS), 2010)
We discuss recent developments in the literature that studies how the dynamics of earnings and wages affect consumption choices over the life cycle. We start by analyzing the theoretical impact of income changes on consumption - highlighting the role of persistence, information, size and insurability of changes in economic resources. We next examine the empirical contributions, distinguishing between papers that use only income data and those that use both income and consumption data. The latter do this for two purposes. First, one can make explicit assumptions about the structure of credit and insurance markets and identify the income process or the information set of the individuals. Second, one can assume that the income process or the amount of information that consumers have are known and tests the implications of the theory. In general there is an identification issue that is only recently being addressed, with better data or better 'experiments'. We conclude with a discussion of the literature that endogenize people's earnings and therefore change the nature of risk faced by households.
Keywords: 330; Einkommen; Lohn; Risiko; Information; Konsum; Lebenszyklus; Theorie